PERAN BRAND IMAGE MEMEDIASI PENGARUH WORD OF MOUTH (WOM) TERHADAP NIAT BELI KONSUMEN PADA JOLLY BAKERY WONOGIRI - Sinta, Ilma; Puji Lestari, Sri Isfantin; Citra Perdana, Dian Noor (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the role of brand image in mediating the influence of word of mouth (WOM) on consumers' purchase intentions at Jolly Bakery Wonogiri. The research uses a non-probability sampling technique, also known as purposive sampling, which is deliberate and subjective. The research method applied is quantitative, using the Smart-PLS 3.0 application as a tool to analyze the collected data. The results of the study show that Word of Mouth influences Purchase Intentions at Jolly Bakery, Wonogiri. Word of Mouth does not influence Brand Image. Brand Image affects Purchase Intentions at Jolly Bakery, Wonogiri. As an intervening variable, Brand Image weakens the influence of Word of Mouth on Purchase Intentions at Jolly Bakery, Wonogiri. Keyword : brand image, word of mouth, consumer purchase intention.